Fatal Injury Caused by a Ram (Ovis Aries) Attack. Issue 5 (10th August 2015) - Škavić, Petar; Šprem, Nikica; Kostelić, Antun
Abstract Animal‐inflicted injuries to humans are a major public health problem around the world resulting in great morbidity, money loss, and mortality. They are related to wild and domestic animals alike. Animals can cause injuries by various mechanisms—biting, stinging, crushing, goring, stomping, butting, kicking, pecking, etc. We present a case of a ram's attack with fatal consequences. A 4‐year‐old, 120 kg jezersko‐solčava breed ram with prior history of aggressive behavior inflicted multiple injuries to his 83‐year‐old owner, who died in the hospital a few hours later due to severe blunt force injuries sustained in the attack. The autopsy revealed the cause of death to be multiple injuries of the thorax and the head. Sheep, even though they are not considered aggressive or large farm animals such as cattle and horses, can inflict serious injuries with devastating results.